Mitochondrial AAA+ protease activity uncovers differential sensitivity of Drosophila blood cell lineages to systemic cues - Batabyal, Rajarshi; Sharma, Aman; Inamdar, Maneesha S. (Frontiers in Cell and Developmental Biology, 2025)
Hematopoiesis involves balanced blood progenitor proliferation, differentiation, and death, in response to dynamic physiological cues. Previous studies have shown that Drosophila lymph gland blood progenitors reside in functionally distinct compartments. Mitochondrial fission-fusion balance and maturity also vary among progenitor compartments and affect cell fate and lineage choice. Here, we show that perturbing mitochondrial homeostasis in Drosophila blood cells (hemocytes), can have multiple long-range effects on lymph gland hematopoiesis. Specifically, depletion of the mitochondrial AAA+ proteases AFG3L2 or YME1L from the niche or blood progenitors, caused larval lethality. However, depletion from hemocytes alone, gave viable larvae but with a histolysed primary lobe, and an intact and expanded niche. Posterior lobes showed severe hyperproliferation and precocious differentiation. Genetic or pharmacological reduction of ROS restored LG size and differentiation status to control levels, while reducing Hippo pathway activity partially rescued the precocious differentiation. Our study provides the first insights into the roles of mitochondrial AAA+ proteases in mediating generation or modulation of systemic signals that control inter-compartmental cross talk between hemocytes and the hematopoietic organ. We propose that mitochondrial homeostasis in hemocytes is a key point of control that helps restrict progenitor differentiation. Given the conservation in AAA+ protease functions and in signaling pathways that control hematopoiesis, our studies will help gain insight into systemic control of mammalian hematopoiesis.